This is how we did it-Conceiving and continuing a body donation and honor program at all india institute of medical sciences, Raipur, India - Abu Ubaida Siddiqui; Dhyanesh Kumar Sharma; Soumitra Trivedi; Manisha Barnwal Sinha; Mrithunjay Rathore (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: Medical institutes around the world are facing scarcity of cadavers for anatomy dissection and teaching purpose. The academic value of "hands-on experience" on human bodies remains the mainstay of medical education, especially in the foster years of the young student. Efforts are needed to improve the availability of human bodies for dissection. This can be achieved by encouraging the masses to donate their bodies for the same. Material and Methods: The authors conceived a full-fledged body donation awareness campaign starting from 2013, which is successfully continuing till date. The program included memorial services and honor ceremonies for the family members of the pledgers/donors. Considerate support was provided by many nongovernmental organizations as well as the administration of the institute in discussion. Observations: The efforts made by the department emerged as an extremely improved scenario in terms of availability of cadavers for anatomy teaching and interdepartmental activities. Till date, 1,106 people have pledged for donating their bodies to the institute and 85 actual donations occurred till 31 July 2019. The continuous efforts of all the stakeholders have significantly improved the cadaver availability in the department where the ratio of one human body to 10 students is being practiced. Conclusions: Further work is still needed to encourage more people toward this altruistic act. Further deliberations with religious and political leaders are underway to enhance the penetration of this message amongst the masses. Extensive publicity is being planned for the same, and the authors are hopeful of further promising results toward this cause.